Adolescent experiences of app-integrated therapy. (26th July 2020) - Gindidis, Simone; Stewart, Sandra E.; Roodenburg, John
Abstract: Smartphone ownership estimates indicate the vast majority of young people are engaging with smartphone devices. The medium offers a promising opportunity for psychologists to connect with young people seeking help to traverse challenges with mental health, behaviour, learning and wellbeing. However, the views of young people using apps alongside face-to-face therapy remain largely unexplored. Given that clients make the single strongest contribution to therapeutic outcomes it is important to consider the perspectives of adolescents in clinical settings. Using semistructured qualitative interviews, the experiences of seven Australian secondary school-aged adolescents (12–18 years) involved in app-integrated therapy were explored. Thematic analysis resulted in the identification of eight key themes: Between-sessions, Introduction, Responsive, Age, Mindfulness-Meditation, Connection, Knowledge, and App features. Recommending apps appears to encourage young people to take ownership of their therapy, affording opportunities for self-reflection and rehearsal of valuable skills. Further research focused on understanding the views of young people utilising apps with therapy is needed to maximise potential therapeutic benefits. Preliminary practice recommendations and future research directions are proposed.